Moving from Graduation to Post-graduation in Portuguese Universities: Changing Literacy Practices, Facing New Difficulties - Carvalho, José Brandão (Journal of Academic Writing, 2012)
<span style="font-family: "Arial","sans-serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In this article we analyse Portuguese postgraduate students’ problems and difficulties when performing written tasks in the context of postgraduate programmes. The data presented are the result of a study based on two different data collection procedures: a) the analysis of students’ written work, organised in a portfolio; b) a questionnaire focussing on the difficulties encountered when performing different tasks involving writing: note-taking; planning a text; writing and editing a text (a literature review); and referencing and quoting according to a reference style (APA). The analysis of students' work revealed problems and difficulties in different areas, namely with selecting information, planning the text, and writing the literature review using academic writing conventions. When asked about the reasons for those problems, students often referred to the difference between the literacy tasks they were used to performing in their undergraduate studies and those that they are requested to develop at the postgraduate level. These differences seem particularly relevant when those tasks are related to assessment practices. At undergraduate level, assessment is often based on examinations while at postgraduate level, it is more dependent on the production of other genres such as literature reviews or essays.